The Effect of Integrity, Work Culture, Knowledge of Audit Techniques, and Task Commitment Toward The Performance of Customs and Excise Auditors - Djaali Djaali; Maruf Akbar; Karuna Karuna (Journal of Business and Behavioural Entrepreneurship, 2017)
The objective of this research is to get about the effect of integrity, work culture, knowledge of audit techniques, and task commitment toward the performance of customs and excise auditors. The research was conducted using survey method with quantitative approach. The size population in this research is 210 at customs and excise auditors. Research sample were selected as mush as 140 auditors using simple random sampling technique. The data obtained with questionnaires and test. The data analyzed using path analysis technique. The finding show that integrity, work culture, knowledge of audit techniques and task commitment have positive direct effect toward the performance of customs and excise auditors. Integrity, work culture and knowledge of audit techniques have positive direct effect toward the task commitment. Integrity and knowledge of audit techniques have positive direct effect toward work culture.